Napoleon Entrée dans Berlin - Madou, Jean-Baptiste, 1796-1877 (artist):::Creator:::::::::::: (Belgium; Brussels)
Depiction of Napoleon entering Berlin, part of a series of prints by Jean-Baptiste Madou depicting the life of Napoleon.